Characterization of Bioactive Compounds from Moringa Leaves and Their Application in High-Antioxidant Functional Drinks - Sembiring, Terkeliat (Jurnal Teknologi dan Ilmu Pertanian, 2025)
Moringa oleifera leaves are known to be rich in bioactive compounds such as polyphenols (main flavonoids: quercetin, kaempferol, myricetin), vitamins (A, C), minerals, and essential amino acids[27][28]. This study characterized the main phytochemical components of Moringa leaf extract and evaluated the formulation of a high-antioxidant functional drink based on the extract. High-Performance Liquid Chromatography (HPLC) assay identified the dominant compounds: quercetin-3-O-glucoside (≈960 µg/g), kaempferol (≈840 µg/g) and rutin (≈835 µg/g) in dried leaves[29][30]. The in-vitro antioxidant activity (DPPH, FRAP) of Moringa leaf aqueous extract reached IC₅₀ 50 µg/mL, comparable to ascorbic acid, indicating a strong radical scavenging capacity. The extract was formulated into a functional drink (moringa leaf infusion + orange juice) with a total phenolic content of 0.45 mg/mL and DPPH scavenging activity of 45% at a dose of 0.5 mg/mL[31][32]. Hedonic tests on 50 panelists showed good taste acceptance (score >80%) after the addition of honey as a natural sweetener. In vivo test results in mice on a high-fat diet showed that supplementation of moringa leaf infusion reduced liver malondialdehyde levels and improved glucose tolerance, indicating potential antioxidant and anti-metabolic syndrome[33][34]. In conclusion, moringa leaves are rich in bioactive compounds with high antioxidant activity; their application in functional drinks can provide health benefits as a source of natural antioxidants.